Activation of MSK-1 exacerbates neuropathic pain through histone H3 phosphorylation in the rats’ dorsal root ganglia and spinal dorsal horn - Li Wang; Yan Gao; Yiming Qiao; Xueli Wang; Zongyi Liang; Ji-Tian Xu; Liren Li (Brain Research Bulletin, 2024)
The exact mechanism underlies the development of neuropathic pain is not yet completely understood. Mitogen and stress-activated kinase 1 (MSK-1) is an important downstream kinase of the mitogen-activated protein kinase (MAPK). It has been extensively studied in the central nervous system, but whether MSK-1 is associated with the neuropathic pain remains elusive. In this experiment, Lumbar 5 spinal nerve ligation (SNL) was used to establish a neuropathic pain condition in the rats. Western blotting, qRT-PCR, immunohistochemistry, intrathecal catheterization and drugs delivery were evaluated to study the physiological responses of the animals. The results showed that SNL resulted in elevated phosphorylated MSK-1 (p-MSK-1) expression in the ipsilateral dorsal root ganglion (DRG) and the spinal dorsal horn in rats, while total MSK-1 (t-MSK-1) did not change significantly. Intrathecal injection of the MSK-1 inhibitor SB747651A partially reversed established neuropathic pain. Additionally, intrathecal administration of MSK-1 siRNA either preoperatively or 7 days postoperatively relieves the development and maintenance of pain, respectively. Meanwhile, the expression levels of p-H3S10, a downstream target of MSK-1, also displayed a significant increase after SNL. And these changes could be reversed by using MSK-1 siRNA. Collectively, the increase of MSK-1 induced by SNL participates in the development and maintenance of neuropathic pain by regulating the expression of p-H3S10 in DRG and spinal dorsal horn. Concentrating on MSK-1 may result in a novel approach to the treatment of neuropathic pain.